Filsafat Pendidikan Progresivisme dalam Pembentukan Karakter Siswa Sekolah Dasar - Sahra Ningrum; Fitri Nurfiani; Ahmad Ruslan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research aims to explore the application of progressivism principles in the formation of student character in elementary schools. The research method used in this research is qualitative research with a descriptive approach. Data was collected through a literature review of various scientific journals, articles and publications from 2019 to 2024. The data collection process involved analysis of trusted sources related to the implementation of progressivism philosophy in basic education. The collected data was then analyzed using thematic analysis techniques, which aim to identify patterns, relationships and main findings related to the influence of progressivism philosophy on the formation of student character in elementary schools. The research results show that progressive learning is effective in developing character values, such as a sense of responsibility, cooperation and social awareness. Integrating the philosophy of progressivism in elementary school education can be an important strategy for forming a generation that is critical, creative and ready to face future challenges.